Implementation of the Merdeka Curriculum in Differentiated Learning on Civics Learning Outcomes of Fourth Grade Students at SD Negeri 08 Kinali - Lusi Putri; Nofriza Efendi; Gingga Prananda; Ayunis Ayunis (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study is motivated by the demands of the Merdeka Curriculum, which emphasizes student-centered learning, one of which is through differentiated instruction. In the context of Civics Education (PKN), this approach is essential to accommodate differences in students' abilities, interests, and learning styles. The aim of this research is to describe the implementation of the Merdeka Curriculum through differentiated instruction and its impact on the PKN learning outcomes of fourth-grade students at SD Negeri 08 Kinali. The research employed a descriptive qualitative method. Data were collected through observations, interviews with teachers and students, and documentation of learning outcomes. The research subjects consisted of one fourth-grade teacher and 25 students. The results of the study show that the teacher applied differentiated instruction in three main aspects: content, process, and product. The strategies used successfully increased students’ active participation and engagement in the learning process. The PKN learning outcomes showed significant improvement in both conceptual understanding and civic attitudes. Challenges encountered included time constraints and the need to enhance teachers’ capacity to design effective differentiated learning. The conclusion of this study is that the implementation of the Merdeka Curriculum through differentiated instruction has a positive contribution to improving students' learning outcomes in PKN. Continued support from the school and teacher training is necessary to optimize this approach in classroom practice.